Konsep pemikiran Mohammed Arkoun dalam aina huwa alfikr al-islÄmiy al-mu'Äshir - Rasyid, Ruslan; Djafar, Hilman (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2019)
Mohammed Arkoun's thought in his monumental work, "aina huwa al-fikr al-islÄmiy"was inspired by two famous Muslim intellectuals, Imam Ghazali and Ibn Rusyd. Arkoun'swork is an idea that spurs the spirit of contemporary Muslims to think ahead by using all thepotential they have so that it can make Islam a religion that can adapt to the development ofthe times or in a religious language called shÄlihun likulli makÄnin wa shÄlihun likulli zamÄnin.In addition, the concept of thought in the work is aimed primarily at opening up broaderhorizons of Arabic Islamic thought and can be used as a method of understandingcontemporary social science based on Islamic views. One effort undertaken by MohammedArkoun is to consolidate modern historical methodology with classical Islamic thought,because for Arkoun that is the only way to achieve a scientific understanding of the historicalthe reality of Islamic society. The perceived impact is the disappearance of all disputes, bothracial and religious. Some of the directions of his thinking are as follows: 1) Arkoun's way ofperceiving himself; 2) Agendas that must be implemented include building an appliedIslamology / islÄmiá»¹Ät tathbÈ‰qhiá»¹ah by trying to apply scientific methodology to the Koran;3) The Western way (alGharb) knows Islam; 4) Return to the starting point; 5) Secularismand Islam; 6) Islam, Science, and Philosophy; 7) Islam and Human Rights; 8) Sufism;9) European nationalism; 10) Think openly.